Development of a Halal Broiler Supply Chain Model: HABITS (HalalHygiene Assurance, Blockchain-Integrated Traceability System) - Hamdi, Muhammad; Ikawati, Retty (Jurnal Dinamika Manajemen, 2025)
This study aims to develop and validate the Halal-Hygiene Assurance, Blockchain Integrated Traceability System (HABITS) model, which incorporates HACCP, SNI 99001:2016, and blockchain technology to ensure traceability and compliance in broiler supply chains. Grounded in resource orchestration and institutional theory, this study utilized a convergent mixed-methods design. Analytic Hierarchy Process (AHP) and compliance gap analysis were employed to develop and assess the model. The findings reveal that transparency and compliance were prioritized over traditional traceability metrics. Significant gaps were identified in blockchain implementation (100% noncompliance),  HACCP integration (42% noncompliance), and SNI 99001:2016 (38% noncompliance), primarily due to cost and infrastructure barriers. The HABITS model extends resource orchestration to religious-cultural contexts, enhancing operational performance and institutional legitimacy.